Towards the New AusGeoid Model - Featherstone, Will; Sproule, David; Goos, J; Kirby, Jonathan; Kuhn, Michael; Claessens, Sten (Spatial Sciences Institute, 2005)
Since November 1998, all high-precision GPS users in Australia have adopted the AUSGeoid98 gravimetric geoid model to transform GPS-derived ellipsoidal heights to the Australian Height Datum (AHD) and vice versa. Since AUSGeoid98 was released by Geoscience Australia (http://www.ga.gov.au/nmd/geodesy/ausgeoid/) based on recommendations by the first-named author, several new theories have been formulated and refined datasets have been released, all of which can improve the Australian geoid model. This paper reports our latest implementations of these theories and datasets, which comprise a global geopotential model derived from the GRACE (Gravity Recovery And Climate Experiment) dedicated satellite gravimetry mission, gravimetric terrain corrections from the version-2 DEM-9S 9"x9" digital elevation model, approximately 200,000 additional land gravity observations in Geoscience Australia's database, improved gravity data cleaning methods, refined marine gravity data from multi-mission satellite radar altimetry, a least-squares crossover adjustment of ship-track gravity observations, and new GPS data collected by State and Territory geodetic survey agencies at key tide-gauges, some junction points and other benchmarks of the AHD. The refined gravimetric geoid solution will be fitted to the GPS-AHD data using least-squares collocation so as to deliberately provide a more direct transformation to the AHD that obviates the need to occupy nearby AHD benchmarks during a GPS survey. This pragmatic solution, while not producing a classical equipotential geoid model, does provide a very useful product for GPS users in Australia until the AHD is rigorously redefined. Our results show that the new model will deliver GPS-derived AHD heights with an RMS of less than ~12 cm in an absolute sense over most parts of Australia, which reduces when used in relative mode over shorter GPS baselines. In short, the new model will deliver height results that are commensurate with or better than Australian class LC (third order) geodetic levelling methods. As with AUSGeoid98, this new product will be released and administered by Geoscience Australia based on our recommendations, hopefully towards the end of 2005.